2018
DOI: 10.1371/journal.pone.0199630
|View full text |Cite
|
Sign up to set email alerts
|

Genetic combining ability of coriander genotypes for agronomic and phytochemical traits in response to contrasting irrigation regimes

Abstract: Knowledge of genetic combining ability and gene action would help breeders to choose suitable parents and devise an appropriate breeding strategy for coriander. In the present study, six diverse genotypes of coriander, their 15 F1s and 15 F2s were evaluated through randomized complete block design with three replications to study genetic combining ability for agronomic and phytochemical traits in coriander. Plants were subjected to well-watered (WW), mild water-deficit stress (MWDS) and severe water-deficit st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
4
9
0
Order By: Relevance
“…The significant interaction effects of GCA and SCA with irrigation regimes on the majority of the studied traits indicated different responses among the parental lines and their crosses to change in irrigation regimes in terms of the expression of these traits. These findings are in agreement with the significant interactions of GCA and SCA with different environments reported elsewhere (Dos Santos et al., 2016; Gholizadeh et al., 2018; Mageto, Makumbi, Nioroge, & Nyankanga, 2017). It is, therefore, necessary to evaluate the genotypes and to estimate the relevant genetic parameters under each irrigation regime to identify the parents and crosses appropriate for genetic improvement of drought tolerance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant interaction effects of GCA and SCA with irrigation regimes on the majority of the studied traits indicated different responses among the parental lines and their crosses to change in irrigation regimes in terms of the expression of these traits. These findings are in agreement with the significant interactions of GCA and SCA with different environments reported elsewhere (Dos Santos et al., 2016; Gholizadeh et al., 2018; Mageto, Makumbi, Nioroge, & Nyankanga, 2017). It is, therefore, necessary to evaluate the genotypes and to estimate the relevant genetic parameters under each irrigation regime to identify the parents and crosses appropriate for genetic improvement of drought tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is essential to develop safflower cultivars that can be successfully cultivated in arid and semi-arid areas. Successful development of drought-tolerant cultivars presupposes a careful study to determine inheritance of traits in the target environment because water deficit stress might affect gene action (Gholizadeh, Dehghani, Khodadadi, & Gulick, 2018;Khodadadi, Dehghani, & Javaran, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Apiaceae family contains additional economically important plants, such as ajwain, angelica, anise, asafoetida, caraway and chervil (Feng et al, ; Que et al, ; Shelef, ). In recent years, a large number of studies have been reported on the phenotype, physiology, stress resistance, gene expression and metabolite identification of coriander (Abbassi et al, ; AlQuraidi et al, ; Choudhary et al, ; Divya et al, ; Fraser et al, ; Gholizadeh et al, ; Verma et al, ). However, among all the Apiaceae species, only the carrot genome has been sequenced until now (Iorizzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The poly-unsaturated fatty acids including linoleic acid and oleic acid are the most important fatty acids in the oil of sun ower. The poly-unsaturated fatty acids plays a fundamental role in human nutrition, and they are important for reducing cholesterol and heart disease (Gholizadeh et al, 2018). Due to the economic importance of sun ower, the developments of effective hybrids are required with superior yield and quality traits.…”
Section: Introductionmentioning
confidence: 99%